Treatment of cervical dysplasia - Arana A., Julio (2015)
The treatment of cervical dysplasia is subject to the following factors: 1. Age and parity of the patient. 2. Severity of dysplasia. 3. gynecological disease breakthrough. 4. Possibility of effective monitoring.